2010
DOI: 10.1016/j.ydbio.2009.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Foregut separation and tracheo-oesophageal malformations: The role of tracheal outgrowth, dorso-ventral patterning and programmed cell death

Abstract: Foregut division—the separation of dorsal (oesophageal) from ventral (tracheal) foregut components—is a crucial event in gastro-respiratory development, and frequently disturbed in clinical birth defects. Here, we examined three outstanding questions of foregut morphogenesis. The origin of the trachea is suggested to result either from respiratory outgrowth or progressive septation of the foregut tube. We found normal foregut lengthening despite failure of tracheo-oesophageal separation in Adriamycin-treated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 51 publications
4
77
1
Order By: Relevance
“…Dynamic ventral-dorsal shift in Shh signaling is required for the onset of tracheo-esophageal separation and foregut morphogenesis. Spatio-temporal disruption or shift of Shh expression is frequently associated with diminished apoptosis of the lateral epithelial ridges and the failure of tracheo-esophageal separation [Ioannides et al, 2010]. In absence of Shh, mice display a spectrum of foregut malformations, including lung hypoplasia and various defects in the trachea and esophagus.…”
Section: Tracheoesophageal Fistulamentioning
confidence: 99%
“…Dynamic ventral-dorsal shift in Shh signaling is required for the onset of tracheo-esophageal separation and foregut morphogenesis. Spatio-temporal disruption or shift of Shh expression is frequently associated with diminished apoptosis of the lateral epithelial ridges and the failure of tracheo-esophageal separation [Ioannides et al, 2010]. In absence of Shh, mice display a spectrum of foregut malformations, including lung hypoplasia and various defects in the trachea and esophagus.…”
Section: Tracheoesophageal Fistulamentioning
confidence: 99%
“…The trachea and lung both arise from an Nkx2-1 þ region of the foregut and presumably from a common progenitor population (reviewed in Cardoso and Lu, 2006). However, the trachea does not undergo branching morphogenesis, rather it separates from the future esophagus by means of a process of septation (Ioannides et al, 2010). Indeed after the initial specification of the Nkx2-1 þ anterior foregut domain, the lung and trachea have somewhat different patterns of gene expression.…”
Section: An Overview Of Lung Developmentmentioning
confidence: 99%
“…In mice, Sox2 is required for normal morphogenesis and homeostasis of diverse tissues, including neural stem cells; retinal stem cells taste buds; hair sensory follicles in the ear; and epithelia of trachea, lung, and esophagus (15)(16)(17)(18). In humans, Sox2 mutations are associated with eye and tracheal/esophageal malformations (18)(19)(20). Recent studies demonstrated that Sox2 is amplified in human lung and esophageal squamous cell carcinomas (21)(22)(23).…”
mentioning
confidence: 99%